Mezi slovem a obrazem teorie a praxe filmové adaptace literárního díla - Bubeníček, Petr, 1973- (2007)
Between Word and Image: Theory and Practice of Film Adaptation The analysis of the phenomenon of adaptation poses a fundamental question: how to practically address a widespread phenomenon that has not yet been paid systematic attention to in the context of Czech literary criticism. Critical reading of structuralist and post-structuralist metatexts of Anglo-American literary and film theoreticians led me to methods on the basis of which it was possible to analyse the selected film adaptations of literary works. This also presents the basis of the division of the thesis. In the first part of the work, I search for models of interpretation, while in the second part, I use these models to analyse the individual adaptations. As part of the primary considerations regarding adaptation, it was necessary to cope with a number of prejudices that have been influencing scholarly work and criticism. Literature, being a long-lived and time-tested medium, appears to be more valuable than film that